Hubungan frekuensi stroke dengan fungsi kognitif Di rsud arifin achmad - Sri - Rahayu; Wasisto - Utomo; Sri - Utami (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The aim of this research was to identify correlation between frequency of stroke and cognitive function in Arifin Achmad hospital Pekanbaru. This research design was by using correlational method with cross sectional study. The research was conducted in Flamboyan room of Arifin Achmad hospital Pekanbaru on 33 respondents. The sampling method using consecutive sampling technique. Measuring instrument used modification of standard observation sheet that has been modified: Mini Mental State Examination (MMSE), which consist of 6 items related to assessment of cognitive function for stroke patients. The data was analyzed by univariate analysis and bivariate analysis by using Fisher test. From the statistic data, ρ value  (0,02) <a (0,05). It meant that there was correlation between frequency of stroke and cognitive function in Arifin Achmad hospital Pekanbaru. Based on these results, the researcher suggests to the health institution to provide nursing care that consider the cognitive function of patients so the patients can take the prevention steps to prevent recurrent stroke. Keywords              : Cognitive function, frequency of stroke, MMSE, stroke patients